Reality Check : Forecasting Growth in the Middle East and North Africa in Times of Uncertainty - Gatti, Roberta; Lederman, Daniel; Islam, Asif M.; Wood, Christina A.; Fan, Rachel Yuting; Lotfi, Rana; Mousa, Mennatallah Emam; Nguyen, Ha (Washington, DC: World Bank, 2022)
The Middle East and North Africa economies face an uncertain recovery. The war in Ukraine presents significant challenges to the global economy and the MENA region. Inflationary pressures brought about by the pandemic are likely to be further exacerbated by the conflict. The potential for rising food prices is even higher, which is likely to hurt the wallets of the poor and vulnerable in the region. The COVID-19 pandemic continues to cast a shadow. As the latest variant sweeps over the region, countries grapple with a host of problems depending on initial conditions and policy priorities. The region, like the rest of the world, is not out of the woods yet. Vaccinations remain the effective path out of the pandemic, leading to lower hospitalizations and death rates. Testing helps curb the spread. During times of uncertainty, it is important to not be overconfident about the region’s growth prospects. Growth forecasts serve as a significant signpost for policymakers to chart a path forward. Over the last decade, growth forecasts in the MENA region have often been inaccurate and overly optimistic, which can lead to economic contractions down the road due to ebullient borrowing. There is considerable room for the region to improve its forecasts that are largely hindered by opaque data systems, growth volatility and conflict. The MENA region lags considerably in the timely production of credible statistics. A key finding of the report is that the best way to improve forecasters is to provide forecasters with as much good quality information as possible.